Training technologies-guarantee of sustainable development of Uzbekistan - Kholmatova Ziroat Anvarovna (Research Parks Publishing LLC, 2020)
Targeted activities have been organized to introduce distance learning into professional development processes, including remote training of teachers using on-line and off-line technologies based on the national e-education network. To achieve a radical improvement of quality of training specialists with higher education, demanded in industries and spheres of economy, through the modernization of material-technical base of higher educational institutions, equipping them with the most modern teaching and laboratory equipment, optimization of areas and specialties of training of qualified personnel, further improvement of technology training, modern curriculum, the Decree of the President of the Republic of Uzbekistan dated May 20, 2011